Old Era Continues in Modern World: A Case Report of Scurvy Induced Myopathy in Patient with Chronic Alcoholism - Girish Singhania; Namrata Singhania; Neha Chawla (Case Reports in Medicine)
We report a case of myopathy in a chronic alcoholic patient with scurvy who presented with generalized weakness, myalgias, and arthralgia. Our case raises awareness regarding rare interaction between vitamin C deficiency and myopathy which is seen more commonly in patients with history of chronic alcoholism and low socioeconomic status. Early treatment with vitamin C replacement is helpful in treatment of the disease and its complications.